Developing web apps with Haskell and Yesod : safety-driven web development - Snoyman, Michael (O'Reilly Media, Inc., 2015)
This fast-moving guide introduces web application development with Haskell and Yesod, a potent language/framework combination that supports high-performing applications that are modular, type-safe, and concise. Fully updated for Yesod 1.4, this second edition shows you how Yesod handles widgets, forms, persistence, and RESTful content. Author Michael Snoyman also introduces various Haskell tools to supplement your basic knowledge of the language.